2019
DOI: 10.3390/pathogens8040211
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cell Lysis Among Periodontal Strains of JP2 and Non-JP2 Genotype of Aggregatibacter actinomycetemcomitans Serotype B Is Not Reflected in Dissimilar Expression and Production of Leukotoxin

Abstract: Leukotoxic potential of Aggregatibacter actinomycetemcomitans strains has been studied by the use of several methods, and results differ depending on the methods used. The aim of the present study was to perform a comprehensive examination of the leukotoxic potential of a collection of A. actinomycetemcomitans strains by use of three quantitative methods, Western blotting, ELISA, and mRNA expression assay and compare these results with previous data obtained by a cell lysis assay. A higher leukotoxic potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…There is no golden standard available for quantification of LtxA production in different strains from this bacterium. Jensen and co-workers [ 11 ] applied three different methods for analyses of LtxA production in a collection of serotype b isolates. The results showed that that the JP2 genotype of A. actinomycetemcomitans had an enhanced LtxA production, even though there was a substantial variation between the examined isolates.…”
Section: Host–parasite Interactionsmentioning
confidence: 99%
“…There is no golden standard available for quantification of LtxA production in different strains from this bacterium. Jensen and co-workers [ 11 ] applied three different methods for analyses of LtxA production in a collection of serotype b isolates. The results showed that that the JP2 genotype of A. actinomycetemcomitans had an enhanced LtxA production, even though there was a substantial variation between the examined isolates.…”
Section: Host–parasite Interactionsmentioning
confidence: 99%
“…The obviously very high toxicity may contribute to the infection of a person with no genetic predisposition. Here, it has to be pointed out that leukotoxicity may be different depending on the test method that was used [38]. Variation of leukotoxicity was not only observed among JP2-and non-JP2 genotype of A. actinomycetemcomitans, but also among the methods of Western blotting, ELISA, cell lysis assay, and mRNA expression assay [38].…”
Section: Discussionmentioning
confidence: 99%
“…For studying LtxA expression, various methods have been used over several decades [ 11 , 22 , 44 , 45 , 46 ]. In the present study, methods based on both leukotoxicity and on assessment of the leukotoxin protein levels (checkerboard) revealed similar results, that is, the leukotoxin expression was significantly higher for the JP2 genotype strain, HK1651, the 640-bp deletion type (456-13U) and the 230-bp deletion type (046-19U) as compared to strains Y4, S23A and 575G.…”
Section: Discussionmentioning
confidence: 99%